A ceramic reinforced aluminum-based composite material for automobile brake disc and preparation method thereof
By prefading the porous titanium carbide frame in the aluminum-based composite material for automobile brake discs using a hot press sintering process and melting metal aluminum, the problem of enhancing the agglomeration distribution of phase titanium carbide in the matrix aluminum is solved, the material is lightweight, high-strength, wear resistance and good thermal conductivity is achieved, and the service life of the brake disc is improved.
Patent Information
- Application Number
- CN202310476148.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-04-28
AI Technical Summary
Among the existing aluminum-based composite materials for automobile brake discs, the agglomeration distribution of the enhanced phase titanium carbide in the matrix aluminum, resulting in poor mechanical properties and wear resistance of the material. The amount of titanium carbide is added is small, resulting in limited improvement in hardness and strength, and the wear resistance cannot be significantly improved.
The porous titanium carbide framework is prefabricated by hot press sintering process and metal aluminum is penetrated at high temperature to obtain a titanium carbide-enhanced aluminum-based composite material. The enhanced phase titanium carbide is uniformly distributed in the form of a continuous spatial grid, and the proportion of the two phases in the aluminum-based composite material is adjusted to reduce energy consumption. The microstructure structure of the material is adjusted by adding aluminum powder of different shapes.
The lightweight, high-strength, wear resistance and good thermal conductivity of aluminum-based composite materials are achieved, and the continuous phase is enhanced to have a lubricating effect when the brake reduces friction, reduces material wear and improves fatigue service life.
Smart Images

Figure CN116426795B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of automobile material application, and particularly relates to a ceramic reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof. Background Art
[0002] With the increasing development of the automobile industry, automobile lightweighting is of great significance to reducing automobile weight, fuel consumption, reducing emissions and environmental protection. Brake discs are important braking components of automobiles, which play the role of deceleration or parking. Their braking effect depends on the performance of the material. Aluminum-based composite materials are light and high-strength, have good thermal conductivity and good wear resistance, which not only meet the requirements of brake discs for material service performance, but also contribute to automobile lightweighting.
[0003] Titanium carbide is often used as a reinforcement phase to improve the mechanical properties of aluminum metal because of its high modulus, high hardness, light weight and good lattice matching with aluminum. Based on the current preparation processes, such as powder metallurgy, hot isostatic pressing, spark plasma sintering and liquid manufacturing, the reinforcement phase is agglomerated on the aluminum matrix, which is a key problem that is unfavorable to the mechanical properties and wear resistance of the composite material; secondly, the amount of reinforcement phase titanium carbide added is small, and it is dispersed in the matrix, which not only has a low strengthening effect on the mechanical properties of the material, resulting in limited improvement in its hardness and strength, but also there is no bonding connection between the reinforcement phases. During the friction and wear process, the reinforcement phase is easy to peel off from the matrix, resulting in the wear resistance cannot be significantly improved.
[0004] At present, regarding a silver-based electrical contact material reinforced with a shape memory effect alloy and a preparation method thereof, Patent 1 (CN 115094280A) discloses an aluminum-based composite material for automobile brake discs and a preparation method thereof; Patent 2 (CN115058619A) discloses a nano-titanium carbide reinforced 2024 aluminum-based composite material and a preparation method thereof; Patent 3 (CN 107641743A) discloses a nano-titanium carbide reinforced aluminum-silicon-based composite material and a preparation method thereof; Patent 4 (CN 115505779A) is entitled a preparation method for in-situ generated aluminum-based titanium carbide composite material.
[0005] Patents 1-4 all adopt the preparation process of melting and casting, and their process characteristics are that the raw material formula composition will inevitably introduce impurities (such as oxide inclusions), which will agglomerate at the grain boundaries of the matrix aluminum, affecting the conduction of stress and friction heat, easily causing brittle fracture and affecting the mechanical properties of the material. The doping of impurities makes the composite material low in hardness, easy to be worn, and exhibits poor wear resistance. In addition, the bonding strength between the impurities and the matrix is low. During the friction and wear behavior, the impurities are more easily worn because they cannot coordinate with the deformation of the matrix, resulting in peeling and forming gaps, which promote crack initiation and expansion under the action of stress, and eventually fail. Secondly, the content of added titanium carbide is small, and titanium carbide is distributed in the aluminum matrix in a discontinuous form at the microscopic level, resulting in low hardening efficiency of the material, poor wear resistance, and reduced service life of the material. If the content of added titanium carbide is higher than that of the matrix, agglomeration will occur, making it difficult to fully combine the respective advantages of the two phases (such as the thermal conductivity and toughness of aluminum and the high hardness and wear resistance of titanium carbide). Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a ceramic-reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof, the purpose of which is to obtain an aluminum-based composite material with light weight, high strength, wear resistance and good thermal conductivity by an industrially mature, safe and reliable preparation process with low energy consumption. The present invention provides a titanium carbide-reinforced aluminum-based composite material, which is composed of titanium carbide and aluminum or aluminum alloy without obvious reaction, wherein the volume fraction of titanium carbide is 35-60%, and the balance is aluminum. A titanium carbide porous skeleton is prefabricated by a hot pressing sintering process, and metal aluminum is infiltrated at a high temperature to obtain a titanium carbide-reinforced aluminum-based composite material, wherein the reinforcing phase titanium carbide is uniformly distributed in the aluminum matrix in the form of a continuous spatial grid, and the reinforcing phase titanium carbide can continuously obtain high strengthening efficiency and high damage tolerance. In addition, the porous composite skeleton prepared by hot pressing titanium carbide and aluminum powder or aluminum alloy powder can effectively adjust the proportion of the two phases in the aluminum-based composite material, which can not only reduce the energy consumption of sintering titanium carbide, but also adjust the microstructure of the aluminum-based composite material by adding aluminum powder in different shapes, thereby regulating the different properties of the material, and ultimately achieving a synergistic improvement in the strength, hardness, wear resistance and thermal conductivity of the material. During braking and deceleration friction, the continuity of the reinforced phase can reduce friction and lubricate, thereby reducing the wear of the composite material, while the continuity of the matrix aluminum is beneficial to the heat dissipation of the material, avoiding thermal brittle fracture of the material, and increasing the fatigue service life of the material.
[0007] The preparation process uses hot pressing and sintering to prepare an aluminum-titanium carbide composite porous skeleton, so that nano-titanium carbide can be evenly distributed in three-dimensional space. When metal aluminum is infiltrated at high temperature, the titanium carbide particles are indirectly sintered so that titanium carbide is continuously distributed in the aluminum matrix in the form of a spatial grid. This spatial configuration has high strengthening efficiency and damage tolerance, and can effectively bring into play the performance characteristics of the two phases.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a ceramic reinforced aluminum-based composite material for an automobile brake disc of the present invention comprises the following steps:
[0010] Step 1: ball-milling aluminum powder and nano-titanium carbide powder to obtain a mixed slurry; allowing the mixed slurry to settle, separate the solid and liquid, and then dry to obtain an aluminum-titanium carbide mixed powder;
[0011] Step 2: Hot Pressing and Sintering
[0012] The aluminum-titanium carbide mixed powder or nano-titanium carbide powder is loaded into a hot pressing mold, hot-pressed and sintered in a vacuum environment or a protective atmosphere, and then heat-maintained and pressure-maintained, and cooled in the furnace to obtain a porous skeleton;
[0013] Step 3, high temperature infiltration of aluminum:
[0014] The porous skeleton and metal aluminum in step 2 are placed in a graphite crucible, placed in a vacuum environment or a protective atmosphere for infiltration treatment and heat preservation, and then cooled with the furnace to obtain a nano-TiC reinforced aluminum-based composite material.
[0015] In step 1, the ball milling mixing time is at least 24 hours, and the ball milling speed is 10-60 rpm; the ball milling is performed by dry or wet ball milling; the solvent used in the wet ball milling is alcohol, the ball milling medium used is zirconium oxide ball, and the material-ball ratio is (5-10):1;
[0016] The aluminum powder and nano-titanium carbide powder in step 1, wherein the aluminum powder is flaky or spherical aluminum powder, or flaky or spherical aluminum alloy powder, and the particle size of the aluminum powder or aluminum alloy powder is 5-50 μm; when the aluminum powder or aluminum alloy powder is flaky, the sheet diameter is 5-30 μm and the thickness is 0.1-2 μm; when the aluminum powder or aluminum alloy powder is spherical, the spherical diameter is 5-15 μm; the particle size of nano-titanium carbide is 20-100 nm; the volume fraction of the aluminum powder in the mixed powder is 0-50 vol%;
[0017] The drying in step 1 is: natural air drying or placing in a fume hood for volatilization;
[0018] The hot pressing sintering in step 2 is specifically to increase the temperature from room temperature to the hot pressing sintering temperature at a heating rate of 5 to 10°C / min. When the temperature reaches the sintering temperature, the pressure is loaded to 5MPa, and the heat preservation and pressure holding time is 1h, and then the furnace is cooled and the pressure is kept to room temperature; the porous skeleton is specifically, when the aluminum-titanium carbide mixed powder is loaded into the hot pressing mold, the obtained porous skeleton is an aluminum-titanium carbide composite porous skeleton, and the temperature of hot pressing and sintering the aluminum-titanium carbide composite porous skeleton is 550-600°C; when the nano-titanium carbide powder is loaded into the hot pressing mold, the obtained porous skeleton is a titanium carbide porous skeleton, wherein the temperature of hot pressing and sintering the titanium carbide porous skeleton is 1000-1300°C;
[0019] The vacuum degree of the vacuum environment in step 2 and step 3 is not higher than 10 -3 Pa, the protective atmosphere is argon;
[0020] The mass ratio of the aluminum-titanium carbide composite porous framework to the metal aluminum in step 3 is not less than 1:3;
[0021] The infiltration in step 3 is specifically to increase the temperature from room temperature to an infiltration temperature of 900-1000°C at a heating rate of 5°C / min, and the holding time is at least 0.5h;
[0022] The ceramic reinforced aluminum-based composite material for brake discs of the present invention comprises a reinforcing phase titanium carbide and a matrix aluminum; the reinforcing phase titanium carbide of the composite material is evenly distributed in the matrix aluminum without obvious defects, wherein the volume fraction of the reinforcing phase titanium carbide is 35% to 60%, and the remainder is aluminum;
[0023] The hardness of the ceramic reinforced aluminum-based composite material for the brake disc is 1.8-2.1 GPa;
[0024] The bending strength of the ceramic reinforced aluminum-based composite material for the brake disc is 280-580 MPa;
[0025] The fracture toughness of the ceramic reinforced aluminum-based composite material for the brake disc is 10-12 MPa·m1 / 2;
[0026] The thermal conductivity of the ceramic-reinforced aluminum-based composite material for the brake disc is 55-130 W / mK.
[0027] Compared with the prior art, the ceramic reinforced aluminum-based composite material for automobile brake discs and the preparation method thereof of the present invention have the following beneficial effects:
[0028] The present invention provides a ceramic reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof. Lightweight titanium carbide and aluminum are used as raw materials to meet the lightweight characteristics of automobiles. The preparation process is to use hot pressing sintering to prefabricate a composite porous skeleton of titanium carbide and aluminum. The sintering temperature used here is to sinter the metal aluminum to achieve the purpose of composite porous skeleton molding and realize the uniform distribution of titanium carbide powder in three dimensions in space, which greatly reduces the energy consumption required for direct sintering of titanium carbide powder. Then, the metal aluminum is infiltrated at high temperature to obtain an aluminum-based composite material. Nano-titanium carbide can achieve sintering between ceramic phase titanium carbide particles and promote the infiltration of metal aluminum during the high-temperature infiltration process. Microscopically, it is manifested as continuous distribution of titanium carbide in the aluminum matrix. Its organizational structure has the characteristics of high strengthening efficiency and damage tolerance. When braking and deceleration friction is performed, the continuity of the enhanced phase can play a lubricating effect, thereby reducing the wear of the composite material, which is beneficial to improving the fatigue wear life of the material. In particular, by adjusting the amount of aluminum powder added in the mixed powder (0-50vol%), the strength, hardness, toughness and thermal conductivity of the aluminum-based composite material can be regulated to meet the performance requirements of the brake disc under complex friction conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a microstructure diagram of the Al-TiC ceramic reinforced aluminum-based composite material prepared in Example 1 of the present invention;
[0030] Figure 2 is a three-point bending stress-strain curve of the Al-TiC ceramic reinforced aluminum matrix composite material prepared in Example 1 of the present invention;
[0031] Figure 3 This is a microstructure diagram of the Al-60 vol% TiC ceramic reinforced aluminum-based composite material prepared in Example 2 of the present invention;
[0032] Figure 4 This is the XRD result of the Al-60vol%TiC ceramic reinforced aluminum matrix composite material prepared in Example 2 of the present invention;
[0033] Figure 5 is a three-point bending stress-strain curve of the Al-60 vol% TiC ceramic reinforced aluminum matrix composite material prepared in Example 2 of the present invention;
[0034] Figure 6 This is a microstructure diagram of the Ag-45vol%TiC ceramic reinforced aluminum-based composite material prepared in Example 3 of the present invention;
[0035] Figure 7 is a three-point bending stress-strain curve of the Ag-45vol%TiC ceramic reinforced aluminum-based composite material prepared in Example 3 of the present invention;
[0036] Figure 8 This is a microstructure diagram of the Ag-40 vol% TiC ceramic reinforced aluminum-based composite material prepared in Example 4 of the present invention;
[0037] Fig. 9 is a three-point bending stress-strain curve of the Ag-40 vol% TiC ceramic reinforced aluminum-based composite material prepared in Example 4 of the present invention;
[0038] Fig.10 is the K of the in-situ fracture toughness test of Example 3 and Example 4 of the present invention J -R curve. DETAILED DESCRIPTION
[0039] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0040] The specific scheme of the present invention is as follows:
[0041] The embodiment of the present invention provides a ceramic-reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof. The ceramic-reinforced aluminum-based composite material is prepared by uniformly mixing micron-grade aluminum powder and nano-titanium carbide powder, and then hot-pressing and sintering to obtain an aluminum-titanium carbide composite porous skeleton, and finally infiltrating metal aluminum to obtain a titanium carbide-reinforced aluminum-based composite material; the volume fraction of titanium carbide powder in the mixed powder is 30-70 vol%, and the remainder is aluminum powder or aluminum alloy powder. The temperature of hot-pressing and sintering the mixed powder is 550-600°C, the pressure is 5MPa, the heat preservation and pressure holding time is 1h, the temperature of infiltrating metal aluminum is 900-1000°C, and the heat preservation time is at least 0.5h.
[0042] The present invention is further described below by specific experimental examples:
[0043] In the following examples, the same hot pressing sintering furnace and melt infiltration tube furnace were used to prepare aluminum-titanium carbide composite porous skeleton and titanium carbide reinforced aluminum-based composite material respectively.
[0044] Example 1
[0045] This embodiment uses a ceramic reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof, including the following preparation steps:
[0046] Step 1: Preparation of TiC skeleton
[0047] Weigh 40 g of TiC powder with an average particle size of 50 nm and put it into the prepared hot pressing mold. Heat it from room temperature to 1200° C. in a vacuum environment or a protective atmosphere. Keep the mixed powder warm and pressurized for 1 hour. Cool it in the furnace to obtain a porous titanium carbide skeleton.
[0048] Step 2, high temperature infiltration of aluminum block:
[0049] The titanium carbide porous skeleton and the aluminum block are placed in a graphite crucible, placed in a high-temperature furnace in a vacuum environment or a protective atmosphere, raised from room temperature to 900° C., kept warm for 1 hour and cooled with the furnace to obtain an Al-80 vol% TiC composite material.
[0050] Figure 1 This is a microstructure diagram of the Al-80 vol% TiC ceramic reinforced aluminum matrix composite material obtained in Example 1 of the present invention. It can be seen that there are no obvious defects in the composite material and titanium carbide is evenly distributed in the matrix. Figure 2 This is the three-point bending stress-strain curve of the Al-80vol%TiC ceramic reinforced aluminum-based composite material prepared in Example 1 of the present invention. Its bending strength is 570MPa, and its thermal conductivity measured at room temperature is 58.4W / mK. Since the ceramic content is much higher than the matrix aluminum content, the hardness, strength and wear resistance of the material are significantly improved, which can increase the service life of the brake disc. However, the toughness and thermal conductivity of the composite material are lost, which may affect the heat transfer efficiency of the brake disc during the braking process.
[0051] Example 2
[0052] This embodiment uses a ceramic reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof, including the following preparation steps:
[0053] Step 1, preparing Al-TiC mixed powder:
[0054] Weigh 10.8g of 5083Al alloy powder with an average particle size of 24μm, 29.4g of TiC powder with an average particle size of 50nm and 80g of zirconium balls, add alcohol whose liquid level is higher than the mixed powder, mix for 48h on a rolling ball mill, and after the mixing is completed, pour the mixed slurry into a beaker, remove the upper alcohol after the powder is precipitated, and then place it in a fume hood for natural drying. After the alcohol is evaporated, an Al-60vol%TiC mixed powder is obtained;
[0055] Step 2, hot pressing and sintering the mixed powder:
[0056] The Al-60 vol% TiC mixed powder is loaded into a prepared hot pressing mold, heated from room temperature to 580° C. in a vacuum environment or a protective atmosphere, and the mixed powder is subjected to heat and pressure treatment for 1 hour, and then cooled in the furnace to obtain an aluminum-titanium carbide composite porous skeleton;
[0057] Step 3, high temperature infiltration of 5083 aluminum alloy:
[0058] The aluminum-titanium carbide composite porous framework and the 5083 aluminum alloy block are placed in a graphite crucible, placed in a high-temperature furnace in a vacuum environment or a protective atmosphere, raised from room temperature to 900°C, kept warm for 1 hour and cooled with the furnace to obtain an Al-60vol%TiC composite material.
[0059] Figure 3 This is a microstructure diagram of the Al-60 vol% TiC ceramic reinforced aluminum matrix composite material obtained in Example 2 of the present invention. It can be seen that there are no obvious defects in the composite material and titanium carbide is evenly distributed in the matrix. Through characterization, it is found that the hardness value of the Al-60 vol% TiC composite material is 2.1±0.21 GPa. Figure 4 This is the XRD result of the Al-60vol%TiC ceramic reinforced aluminum matrix composite material obtained in Example 2 of the present invention. It can be seen that when the two phases are infiltrated at high temperature, there are no other reaction products. Figure 5 This is the three-point bending stress-strain curve of the Al-60 vol% TiC ceramic reinforced aluminum-based composite material prepared in Example 2 of the present invention. Its bending strength is 337 MPa, and its thermal conductivity measured at room temperature is 97.5 W / mK.
[0060] Example 3
[0061] This embodiment uses a ceramic reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof, including the following preparation steps:
[0062] Step 1, preparing Al-TiC mixed powder:
[0063] Weigh 11.4g of pure aluminum powder with an average flake size of 10-20μm, 24.5g of TiC powder with an average particle size of 50nm and 70g of zirconium balls, add alcohol whose liquid level is higher than the mixed powder, mix for 48h on a rolling ball mill, and after the mixing is completed, pour the mixed slurry into a beaker, remove the upper alcohol after the powder is precipitated, and then place it in a fume hood for natural drying. After the alcohol is evaporated, a mixed powder is obtained;
[0064] Step 2, hot pressing and sintering the mixed powder:
[0065] The mixed powder is loaded into a prepared hot pressing mold, heated from room temperature to 580°C in a vacuum environment or a protective atmosphere, and the mixed powder is subjected to heat and pressure treatment for 1 hour, and then cooled in the furnace to obtain an aluminum-titanium carbide composite porous skeleton;
[0066] Step 3, high temperature infiltration of aluminum:
[0067] The aluminum-titanium carbide composite porous skeleton and the metal aluminum block are placed in a graphite crucible, placed in a high-temperature furnace in a vacuum environment or a protective atmosphere, raised from room temperature to 900°C, kept warm for 1 hour and cooled with the furnace to obtain an Al-50vol%TiC composite material.
[0068] Figure 6 This is a microstructure diagram of the Al-50vol%TiC ceramic reinforced aluminum matrix composite material obtained in Example 3 of the present invention. It can be seen that the flaky aluminum powder in the composite material is oriented and uniformly distributed in the aluminum matrix in a direction perpendicular to the pressure. Through characterization, it is found that the hardness value of the Al-50vol%TiC composite material is 1.8±0.22GPa. Figure 7 This is the three-point bending stress-strain curve of the Al-50 vol% TiC composite material prepared in Example 3 of the present invention. The bending strength is 302 MPa, and the thermal conductivity measured at room temperature is 119.2 W / mK.
[0069] Example 4
[0070] This embodiment uses a ceramic reinforced aluminum-based composite material for automobile brake discs and a preparation method thereof, including the following preparation steps:
[0071] Step 1, preparing Al-TiC mixed powder:
[0072] Weigh 16.2g of pure aluminum balls with an average ball diameter of 10μm, 19.6g of TiC powder with an average particle size of 50nm and 70g of zirconium balls, add alcohol whose liquid level is higher than the mixed powder, and mix on a rolling ball mill for 24h. After the mixing is completed, pour the mixed slurry into a beaker, remove the upper alcohol after powder precipitation, and then place it in a fume hood for natural drying. After the alcohol evaporates, a mixed powder is obtained;
[0073] Step 2, hot pressing and sintering the mixed powder:
[0074] The mixed powder is loaded into a prepared hot pressing mold, heated from room temperature to 550°C in a vacuum environment or a protective atmosphere, and the mixed powder is subjected to heat and pressure treatment for 1 hour, and then cooled in the furnace to obtain an aluminum-titanium carbide composite porous skeleton;
[0075] Step 3, high temperature infiltration of aluminum:
[0076] The aluminum-titanium carbide composite porous skeleton and the metal aluminum block are placed in a graphite crucible, placed in a high-temperature furnace in a vacuum environment or a protective atmosphere, raised from room temperature to 1000°C, kept warm for 1 hour and cooled with the furnace to obtain an Al-40vol%TiC composite material.
[0077] Figure 8This is a microstructure diagram of the Al-40vol%TiC ceramic reinforced aluminum-based composite material obtained in Example 4 of the present invention. It can be seen that there are no obvious defects in the composite material, titanium carbide is evenly distributed in the matrix in the form of a grid, and the matrix aluminum retains a spherical shape, so that the volume fraction of aluminum in the composite material can be controlled. Through characterization, it is found that the hardness value of the Al-40vol%TiC composite material is 1.6±0.1GPa, Fig. 9 is the three-point bending stress-strain curve of the Al-40vol%TiC ceramic reinforced aluminum-based composite material obtained in Example 3 of the present invention, and its bending strength is 285MPa. Fig.10 is the K of the in-situ fracture toughness test of the ceramic reinforced aluminum matrix composite material prepared in Example 3 and Example 4 of the present invention. J -R curve, the results show that the crack propagation in the aluminum-based composite material prepared by the present invention is relatively stable, showing an upward R curve behavior, and the fracture toughness values are 12.5MP·m 1 / 2 and 11.6MP·m 1 / 2 The thermal conductivity measured at room temperature is 138.8W / mK.
[0078] Example 5
[0079] The same as Example 1, except that the nano-titanium carbide powder is hot-pressed and sintered at 1400°C, the pressure is 30MPa, and the heat preservation and pressure holding time is 2h. The prepared titanium carbide skeleton will form too many closed pores in the skeleton due to the high sintering temperature, which will affect the infiltration of metal aluminum, resulting in hole defects in the composite material, resulting in poor strength, hardness and wear resistance of the aluminum-based composite material;
[0080] Comparative Example 1
[0081] The same as Example 2, except that there is no ball milling process in Example 2, only a simple mixing of the two phases, and the uniformity of the mixed powder is poor, so that the aluminum-rich region of the composite material has poor wear resistance and is easily worn and pitted. Not only is the thermal conductivity low, but the braking performance of the brake disc is also deteriorated. The agglomeration of titanium carbide and the difference in the modulus of the two phases are large, which affects the stress conduction of the composite material, resulting in cracking of the two-phase interface and premature failure. Its service performance cannot meet the actual performance requirements.
[0082] Comparative Example 2
[0083] The same as Example 2, except that, in step 2, the hot pressing sintering temperature is 650°C. The aluminum powder in the mixed powder will be squeezed out of the graphite mold due to the high temperature, resulting in a low aluminum content in the porous composite skeleton. Subsequently, the aluminum content in the aluminum-based composite material cannot be regulated, so that the thermal conductivity of the material cannot be improved, which is not conducive to the dissipation of heat in the friction process of the material and causes thermal brittle fracture, and ultimately leads to material failure.
[0084] Comparative Example 3
[0085] The same as Example 2, except that, in step 2, a hot pressing sintering pressure of 20 MPa is adopted. The aluminum powder in the mixed powder will result in a low porosity of the composite skeleton due to excessive pressure, and thus the aluminum content in the aluminum-based composite material cannot be regulated. In addition, the hard phase titanium carbide is subjected to pressure to squeeze the soft phase aluminum out of the gaps between the titanium carbide particles to form a titanium carbide agglomeration phenomenon, which not only reduces the thermal conductivity of the material but also increases the brittleness of the material, making it difficult to synergistically improve and regulate the material performance.
[0086] Comparative Example 4
[0087] The same as Example 2, except that, in step 3, the porous composite skeleton of titanium carbide and aluminum and the aluminum block are directly subjected to melt infiltration treatment at 900°C without a vacuum environment and argon protection. The aluminum in the composite material is oxidized to form a brittle phase aluminum oxide, and the composition of the material changes, causing the hardness, strength, toughness, thermal conductivity and other properties of the composite material to deteriorate.
[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a ceramic reinforced aluminum-based composite material for automobile brake discs, characterized in that: The following steps are involved: Step (1): mixing aluminum powder and nano titanium carbide powder by ball milling to obtain a mixed slurry; allowing the mixed slurry to settle, separate the solid and liquid, and then dry to obtain an aluminum-titanium carbide mixed powder; Step (2), hot pressing sintering: The aluminum-titanium carbide mixed powder or nano-titanium carbide powder is loaded into a hot pressing mold, hot-pressed and sintered in a vacuum environment or a protective atmosphere, and then heat-maintained and pressure-maintained, and cooled in the furnace to obtain a porous skeleton; Step (3), high temperature infiltration of aluminum: The porous skeleton and metal aluminum in step 2 are placed in a graphite crucible, placed in a vacuum environment or a protective atmosphere for infiltration treatment and heat preservation, and then cooled with the furnace to obtain a nano-TiC reinforced aluminum-based composite material; The ceramic reinforced aluminum-based composite material for brake discs comprises a reinforcing phase of titanium carbide and a matrix of aluminum; The reinforcing phase titanium carbide is evenly distributed in the matrix aluminum without obvious defects, wherein the volume fraction of the reinforcing phase titanium carbide is 35% to 60%, and the remainder is aluminum; The ceramic reinforced aluminum-based composite material for brake disc has a hardness of 1.8-2.1 GPa, a bending strength of 280-580 MPa, a fracture toughness of 10-12 MPa·m1 / 2, and a thermal conductivity of 55-130 W / mK; The mass ratio of the aluminum-titanium carbide composite porous framework to the metal aluminum in step (3) is not less than 1:3; the infiltration is specifically carried out from room temperature to an infiltration temperature of 900-1000°C at a heating rate of 5°C / min, and the insulation time is at least 0.5h.
2. The method for preparing a ceramic reinforced aluminum-based composite material for automobile brake discs according to claim 1, characterized in that: The aluminum powder in step (1) is flaky or spherical aluminum powder, or flaky or spherical aluminum alloy powder. When the aluminum powder or aluminum alloy powder is flaky, the diameter of the flakes is 5-30 μm and the thickness is 0.1-2 μm; when the aluminum powder or aluminum alloy powder is spherical, the diameter of the spheres is 5 to 15 μm; the particle size of nano-titanium carbide is 20-100 nm; and the volume fraction of the aluminum powder in the mixed powder is 0-50 vol%.
3. The method for preparing a ceramic reinforced aluminum-based composite material for automobile brake discs according to claim 1, characterized in that: The ball milling in step (1) is performed by dry or wet ball milling; the solvent used in the wet ball milling is alcohol, the ball milling medium is zirconia balls, and the material-to-ball ratio is (5-10):
1.
4. The method for preparing a ceramic reinforced aluminum-based composite material for automobile brake discs according to claim 1, characterized in that: The ball milling mixing time in step (1) is at least 24 hours, and the ball milling speed is 10 to 60 rpm; the drying in step 1 is: natural air drying or placing in a fume hood for volatilization.
5. The method for preparing a ceramic reinforced aluminum-based composite material for automobile brake discs according to claim 1, characterized in that: The hot pressing sintering in step (2) is specifically to heat up from room temperature to the hot pressing sintering temperature at a heating rate of 5 to 10°C / min. When the temperature reaches the sintering temperature, the pressure is loaded to 5MPa, and the heat preservation and pressure holding time is 1h, and then the furnace is cooled and the pressure is kept to room temperature. The porous skeleton is specifically that when the aluminum-titanium carbide mixed powder is loaded into the hot pressing mold, the obtained porous skeleton is a composite porous skeleton of aluminum-titanium carbide, and the temperature of hot pressing and sintering the composite porous skeleton of aluminum-titanium carbide is 550-600°C; when the nano-titanium carbide powder is loaded into the hot pressing mold, the obtained porous skeleton is a titanium carbide porous skeleton, wherein the temperature of hot pressing and sintering the titanium carbide porous skeleton is 1000-1300°C.
6. The method for preparing a ceramic reinforced aluminum-based composite material for automobile brake discs according to claim 1, characterized in that: The vacuum degree of the vacuum environment in steps (2) and (3) is not higher than 10 -3 Pa, the protective atmosphere is argon.
Citation Information
Patent Citations
Nanometer titanium carbide reinforced aluminum silicon-based composite material and preparation method thereof
CN107641743A
Nano titanium carbide reinforced 2024 aluminum-based composite material and preparation method thereof
CN115058619A
Aluminum-based composite material for automobile brake disc and preparation method of aluminum-based composite material
CN115094280A
Preparation method for in-situ generation of aluminum-based titanium carbide composite material
CN115505779A
Si3N4 foam ceramic reinforced aluminum-based composite material and preparation method and application thereof
CN108707771A